Analisa Perbandingan Konduktor ACSR Hawk dan ACCC Amsterdam pada Rekonduktoring SUTET 500 kV di Suralaya-Cilegon - Ujang Wiharja; Muhammad Faqih (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Transmission line reconductoring is one of the strategic solutions to increase the capacity and efficiency of the power system without the need to build new infrastructure. This study aims to analyze and compare the performance of two types of conductors, namely ACSR Hawk and ACCC Amsterdam, used in the Suralaya-Cilegon 500 kV SUTET transmission line. The comparison is carried out by considering technical aspects including power losses, ampacity, horizontal and vertical sag values, and overall energy efficiency. The research methodology involved a literature study, collection of conductor technical data, calculation of resistance, current, and power losses, and simulation of sag values against temperature variations. In addition, economic analysis and field implementation aspects were also considered to assess the feasibility of using each conductor. The results show that Amsterdam's ACCC conductor has superior technical performance compared to Hawk's ACSR. ACCC is capable of delivering currents up to ±1300 A, compared to ACSR Hawk which is only ±800 A. The power loss value using ACCC is recorded at ±1.34 MW, lower than ACSR Hawk at ±1.79 MW. In addition, ACCC exhibits smaller sag values due to its lighter weight and higher tensile stress, making it more stable against temperature fluctuations. In terms of energy efficiency, the use of ACCC can save energy up to ±3942 MWh per year. By considering the technical advantages and long-term energy efficiency, this study recommends the use of Amsterdam ACCC as a reconductoring solution for high-voltage transmission lines, especially in systems that have high loads and require maximum reliability and efficiency.